METODE WEIGHTED MOVING AVERAGE DALAM M-FORECASTING - Akmal Nasution (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2019)
Abstract: M-Forecasting or Mobile Forecasting can be interpreted as mobile-based forecasting. Forecasting here means predicting a situation in the future. The use of mobile technology in forecasting is considered appropriate to improve the efficiency of forecasting to be carried out, this is supported by the development of increasingly mobile technology, where digital marketing marketing research institutions estimate that in 2018 the number of active smartphone users in Indonesia is more than 100 million people. This fantastic amount can be utilized by the development of mobile-based information systems for forecasting. Predictions of a forecast can be realized by using several methods. The Weighted Moving Average method is one of them. This method provides predictions for the future by utilizing previous data and giving different weights for each data used. The level of confidence in forecasting can be determined by measuring the error percentage of the forecasting obtained. The higher the error rate can be interpreted that the forecasting results obtained are increasingly unreliable or inaccurate, and vice versa. This forecasting technique can be applied in various fields of work, including in forecasting rubber production. By obtaining forecasting data on rubber production in the future, of course, it can provide an overview of future work steps, so that it can increase the company's work productivity. Based on this, the researchers intend to build a mobile-based forecasting application system, so that it can be installed in a mobile device later, especially mobile technology with the Android operating system. Keywords: Forecasting, Mobile, Android, Weighted Moving Average. Abstrak: M-Forecasting atau Mobile Forecasting dapat diartikan sebagai peramalan berbasis mobile. Peramalan disini berarti memprediksi suatu keadaan dimasa mendatang. Penggunaan teknologi mobile dalam peramalan dianggap tepat untuk meningkatkan efisiensi peramalan yang akan dilakukan, hal ini didukung dengan perkembangan teknologi mobile yang kian pesat, dimana lembaga riset digital marketing emarketer memperkirakan pada 2018 jumlah pengguna aktif smartphone di Indonesia lebih dari 100 juta orang.  Jumlah yang fantastis ini dapat dimanfaatkan dengan pengembangan sistem informasi berbasis mobile untuk peramalan. Prediksi dari sebuah peramalan dapat terwujud dengan penggunaan beberapa metode. Metode Weighted Moving Average adalah salah satunya. Metode ini memberikan prediksi masa depan dengan memanfaatkan data-data terdahulu dan memberikan bobot yang berbeda-beda untuk setiap data yang digunakan. Tingkat kepercayaan peramalan dapat diketahui dengan mengukur persentase eror dari peramalan yang diperoleh. Semakin tinggi tingkat eror dapat diartikan bahwa hasil peramalan yang diperoleh semakin tidak dapat dipercaya atau tidak akurat, begitu juga sebaliknya. Teknik peramalan ini dapat diterapkan diberbagai bidang pekerjaan, termasuk dalam peramalan produksi karet. Dengan memperoleh data peramalan produksi karet dimasa mendatang tentunya dapat memberikan gambaran untuk langkah-langkah kerja kedepannya, sehingga dapat meningkatkan produktivitas kerja perusahaan. Berdasarkan hal tersebut, peneliti bermaksud membangun sebuah sistem aplikasi peramalan berbasis mobile, sehingga dapat dipasang diperangkat mobile nantinya, khususnya teknologi mobile dengan sistem operasi android.Kata Kunci:    Forecasting, Mobile, Android, Weighted Moving Average.